2008
DOI: 10.1016/j.meegid.2007.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of Schistosoma mansoni: A robust, high-throughput method to assess multiple microsatellite markers from individual miracidia

Abstract: Schistosomiasis is one of the major unconquered infectious diseases afflicting people of developing countries, particularly in Africa. A deeper understanding of the epidemiology of schistosomes is complicated by the intravascular location of adult worms which makes them routinely unavailable for study. Their progeny, miracidia, which are hatched from eggs that are passed in feces, are available and can provide valuable insights about human infections, but they are small in size, hindering robust molecular anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 32 publications
1
38
0
Order By: Relevance
“…Clearly, adult worms cannot be obtained from infected people, but miracidia are accessible. Gower et al (2007) and Steinauer et al (2008) were able to obtain MLGs from individual miracidia of S. mansoni, but this was technically difficult. Characterisation of MLGs from larval stages of S. japonicum has not been reported to date.…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, adult worms cannot be obtained from infected people, but miracidia are accessible. Gower et al (2007) and Steinauer et al (2008) were able to obtain MLGs from individual miracidia of S. mansoni, but this was technically difficult. Characterisation of MLGs from larval stages of S. japonicum has not been reported to date.…”
Section: Discussionmentioning
confidence: 99%
“…The miracidia were lysed individually in the wells of a 96 well plate and genotyped at 12 microsatellite loci as described by Steinauer et al [40]. GenBank accession numbers of the loci include the following: AF325695, AF202965, AF202966, AF202968, L46951, AF325698, AF325694 (Multiplex panel P17) and M85305, R95529, AI395184, BF936409, AI067617 (multiplex panel P22).…”
Section: Methodsmentioning
confidence: 99%
“…An alternative is to genotype directly from miracidia themselves. Freshly hatched miracidia can be held briefly in water before being taken directly on to the genotyping stage if laboratory facilities are immediately available (Beltran et al 2008; Steinauer et al 2008; Valentim et al 2009). However, some sort of storage method is generally required since most samples are field-collected.…”
Section: Introductionmentioning
confidence: 99%
“…Some have PCR-amplified only a single locus for each miracidium (Shrivastava et al 2005), while others have multiplexed several loci within a single reaction per miracidium, and these studies have all used FTA cards (Rudge et al 2008; Gower et al 2007, 2011). A few studies, extracting DNA from freshly hatched miracidia in water or saline, have reported successful amplification of up to 21 loci in four reactions (Steinauer et al 2008; Valentim et al 2009). …”
Section: Introductionmentioning
confidence: 99%